Spatially Resolved Crosslinking of Hydroxypropyl Cellulose Esters for the Generation of Functional Surface-Attached Organogels - Nau, Maximilian; Trosien, Simon; Seelinger, David; Boehm, Anna K.; Biesalski, Markus (Frontiers in Chemistry, 2019)
Chemistry, geometric shape and swelling behaviour are the key parameters that determine any successful use of man-made polymeric networks (gels). Whereas our understanding of the swelling behaviour of both water-swellable hydrogels and organogels that swell in organic solvents can be considered well advanced with respect to fossil fuel-based polymer networks, our understanding, in particular, of wood-derived polymers in such a network architecture is still lacking. In this work, we focus on organogels derived from hydroxypropyl cellulose (HPC) ester. The latter polymer was functionalised with saturated and unsaturated fatty acids, respectively. Due to their tailored chemical constitution, such macromolecules can be crosslinked and simultaneously surface-bound by using a photo-induced radical reaction using a photo-initiator. Based on the choice of fatty acid used in the design of the HPC ester, and by controlling the degree of substitution (DS) obtained during the esterification of the polysaccharide, the physical properties (e.g., polarity) of the resulting gel can be easily manipulated. Depending on the initiator employed, different wavelengths of light, from UV to visible, can be utilised for the crosslinking reaction, which facilitates the deployment of a range of light sources and different lithographic methods. By altering the illumination time, the netpoint density, and thus, the degree of linear deformation in equilibrium and the swelling kinetics, can be easily aligned. Finally, we performed a proof-of-principle experiment to demonstrate the application of our material for the generation of spatially resolved polymer patches to enrich organic molecules from a solution within a microfluidic channel.